Case report: A fatal outcome from co-infection of COVID-19 and dengue in the western region of Jeddah, Saudi Arabia - Al-Nazawi, Ashwaq M.; Al-Zahrani, Ali A.; Qadir, Anjum; Alghamdi, Rana; Tambo, Ernest; Alsahafi, Abdullah (Frontiers in Public Health, 2022)
Introduction: Co-infection COVID-19 and dengue may coexist, as both viruses share similar laboratory and clinical features, making diagnosis and treatment challenging for health care professionals to prescribe and negatively impacts patient prognosis and outcomes. Results and discussions: Both cases were positive for PCR and X ray laboratory investigation at clinical examination confirmingCOVID-19 and dengue co-infection, admission and better management in referral hospitals are presented and discussed. The timeline provided detailed cases situational analysis and medical actions taken and outcomes. Conclusion: Both co-infection cases (patients) health condition had a poor prognosis, diagnosis and ended with the undesired outcomes. Scaling up dual mosquito-vector linked viral diseases surveillance in understanding the transmission dynamics, early diagnosis and case management timely safety monitoring in clinic and hospitals settings nationwide is paramount in curbing preventable co-infections and mortality.